Challenges in reducing group B Streptococcus disease in African settings. Issue 1 (18th October 2016) - Nishihara, Yo; Dangor, Ziyaad; French, Neil; Madhi, Shabir; Heyderman, Robert
Abstract : Group B Streptococcus (GBS) is a leading cause of neonatal sepsis and meningitis in high-income settings and is associated with high rates of neonatal mortality and morbidity. There is now increasing evidence to suggest that there is a high GBS disease burden in resource-limited countries, and it is therefore critically important to identify suitable and practical preventive strategies. In Europe and North America, intrapartum antibiotic prophylaxis (IAP) has led to a dramatic reduction of early-onset GBS disease. However, the methods for identifying pregnant women who should receive IAP and how to reduce late-onset GBS disease are not without controversy and are challenging for most sub-Saharan African countries. GBS vaccines are approaching phase III trials but are still under development. This review aims to explore the current evidence related to strategies for reducing invasive GBS disease in an African setting, the development of a GBS vaccine and whether preventative measures against GBS disease can be practically implemented.